Stochastic Frontier Model for the Evaluation of the Sustainability of Urban Gardens in Puebla, Mexico - Elimelec Muñoz-Nuñez; Omar Romero-Arenas; Sonia Emilia Silva Gómez; Rolando Rueda Luna; Ricardo Munguía Pérez; Manuel Huerta-Lara (Urban Science)
Amid rapid urbanization and persistent food insecurity in Latin America, urban gardens have emerged as sustainable alternatives to conventional agriculture. This study evaluates the technical and economic efficiency of producing four vegetables (lettuce, Swiss chard, spinach, and tomato) in urban and conventional systems in Puebla, Mexico. Using a stochastic frontier model, the analysis integrates key environmental costs, specifically, water-use efficiency and nutrient balance valuation, to assess the sustainability trade-offs. The results show that urban gardens achieve comparable efficiency to conventional systems while reducing water use by up to 66% and optimizing nutrient cycling. These findings support urban agroecological models as viable strategies for local food production and provide actionable insights for municipal policies aimed at enhancing urban food resilience and environmental performance.